Reaction of some chickpea cultivars to Fusarium oxysporum f sp ciceri and Meloidogyne incognita disease complex - K. KRISHNAPPA, V. KRISHNA RAO1 and (Indian Phytopathology, 2002)
All 13 chickpea cultivars were highly susceptible to M. incognita in pot experiments. The cultivars exhibited a differential reaction to the fungus and nematode-fungal pathogen complex. Wilt incidence caused by Fusarium oxysporum alone was on average 28.7% but this rose to 45.1% in the nematode-fungal complex.